Interlanguage Mediated Teaching Within the Multicultural Mathematics Classrooms: A Current Trend Overview Based on Bibliometrics - Nugraha, Danang Satria; Nugraha, Adhi Surya (Jurnal Pendidikan Progresif, 2025)
Abstract: Interlanguage Mediated Teaching Within the Multicultural Mathematics Classrooms: A Current Trend Overview Based on Bibliometrics. Objectives: This study presents an analytical-based overview of the current trends in interlanguage mediated teaching (IMT) within multicultural mathematics classrooms, using a bibliometric analysis of 285 relevant research literature retrieved from the Web of Science database during 2014 – 2024. Methods: By examining the distribution of publications, citation patterns, and influential researchers via VOSviewer, this study identifies key themes and emergent trends in the field. Findings: Centered on the co-occurrence analysis of the 7,065 terms, the present study identifies seven distinctive clusters, i.e., (1) ‘STEM integration and multiculturalism’ (32.83%), (2) ‘equity and access in diverse learning environments’ (20.59%), (3) ‘language acquisition and mathematical achievement’ (17.16%), (4) ‘culturally responsive pedagogy and teacher education’ (11.76%), (5) ‘cultural diversity and learner perceptions’ (7.84%), (6) ‘multicultural classroom dynamics and teacher perceptions’ (7.35%), and (7) ‘self-regulated learning and mathematical achievement’ (2.45%). The analysis of leading researchers reveals a group of individuals who have made significant contributions to the field of IMT within multicultural mathematics classrooms. While the number of publications is relatively small, the researchers have demonstrated a notable impact through their research, as evidenced by the citation counts and total link strength. Conclusion: Qualitative research methods, such as case studies and interviews, could be complement this quantitative-based analysis and postulate a deeper considerate of the implementation and influence of IMT in diverse classrooms. Keywords: applied linguistics, ethnomathematics, interlanguage, multicultural mathematics, multicultural students.